Effect of climatic influences on the migrations of infective larvae of Cyathostominae - I. Langrová; I. Jankovská; M. Borovský; T. Fiala (Veterinární Medicína, 2003)
Migration to herbage of Cyathostominae from experimentally deposited fresh or incubated faecal samples containing a known number of cyathostome L3 was studied in the Czech Republicfor up to 1 year. It was found out that most larvae remained quite close to the faecal samples. Of all larvae recovered from herbage 89.18% were collected within 10 cm of the faeces. Temporal variation in the presence of Cyathostominae larvae on vegetation may account for poor recovery of Cyathostominae L3 in the field. A few infective larvae (0.05?2.74% of the larvae placed on the plot) were found as far as 30 cm from the faeces after 1 or 2 weeks. The number of larvae was significantly higher in June, with maximum recoveries of 4.97% (P < 0.05). Time of day was also significantly related to the number of L3 recovered, larval recovery was greater in the morning than at noontime, the highest number of L3 was observed at 8 am. Moisture and temperature were the most important weather factors associated with lateral larval migrations. There was a closer relation between the larval yields and monthly rainfall (r = 0.47) than between the larval recoveries and weekly rainfall (r = 0.23, r = 0.24). A significant amount of migration occurred during dew. An insignificant amount of migration occurred during dry weather.